Application of Process Hierarchy Analysis as A Direction of Economic Development in West Coast District - Feri Hardani; Toto Gunarto; Neli Aida (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2021)
West Coast District as a district that has just been established must be able to catch up with progress in other areas, of course as a new district, the hope is that this area will expand so that the region can develop more independently and bring prosperity to the residents of the West Coast District, economic development can be done by through community aspirations or what is commonly referred to as community participation in development, so that in the development process the community is involved and the development implemented will be right on the recommendation. This study aims to determine how the perceptions of the people of the West Coast District regarding regional economic development, and which sectors want to become development priorities, with the great potential that the region has, namely tourism which is well known even to foreign countries, making people want the local government to make the tourism sector as a tourism sector. sectors that are prioritized for development. This study uses process hierarchy analysis (AHP), as a method to see people's perceptions of development.Keywords:Strategy; Region, Priority, Economic